2022
DOI: 10.2113/2022/4266697
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Bulk Moduli of Deepwater Reservoir Sands: Influence of Pressure and Fluid Saturation

Abstract: The static bulk modulus of unconsolidated sands is essential for predicting the in situ effective pressure to reduce drilling risks in deepwater reservoirs; however, the dynamic bulk modulus is often more broadly available from seismic or well logging data. Therefore, it is tempting to investigate the relationship between static and dynamic bulk moduli. We perform a series of ultrasonic velocity measurements on 21 deepwater reservoir sands from the Gulf of Mexico (GoM) to study the static and dynamic bulk modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The static bulk modulus symbolizes the mechanical firmness of subsurface basins (Zimmer, 2004;Zoback, 2007). The dynamic moduli can be examined from seismic or well logging data (Fjaer, 2019;Wang et al, 2022). It may be determined using Equation 5.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The static bulk modulus symbolizes the mechanical firmness of subsurface basins (Zimmer, 2004;Zoback, 2007). The dynamic moduli can be examined from seismic or well logging data (Fjaer, 2019;Wang et al, 2022). It may be determined using Equation 5.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many Researchers have worked on bulk modulus; to highlight some findings, Cheng and Johnston (1981) have worked on the static-to-dynamic bulk modulus ratio for dry Navajo and Berea sandstones which differs from about 0.5 at atmospheric pressure to about unity at 200 x 10 6 Pa. Also, Jizba and Nur (1990) concluded that the static bulk modulus is nearly the value of the dynamic modulus at high-stress levels and might decrease to about 50% value of the dynamic bulk modulus at low-stress levels from dry tight gas sandstones constituents (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Bulk modulus is one of the mechanical properties used in several geoengineering problems (Wang et al, 2022;Bock, 1993;Bell, 1996;Andhumoudine, 2021;Yang and Liu, 2021) and it could be obtained by the stress-strain relation (like static measurement) or the propagating elastic wave velocities (such as dynamic measurement) (Wang et al, 2020). The static bulk modulus symbolizes the mechanical firmness of subsurface basins (Zimmer, 2004;Zoback, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the SCS is a typical deep-water basin, exhibiting high pressure and temperature characteristics. Therefore, the rock physical characteristics in SCS might be different from that of other well-studied marginal seas (e.g., Gulf of Mexico, North Sea), hence affecting its corresponding elastic signatures (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%